Maximum carbon uptake potential through progressive management of plantation forests in Guangdong Province, China - Xueyan Li; Chongyuan Bi; Jianping Wu; Chaoqun Zhang; Wenting Yan; Zhenzhen Xiao; Ying-Ping Wang; Jiashun Ren; Yongxian Su (Communications Earth & Environment)
Abstract Forest cover in Guangdong Province, southern China, has doubled over the last four decades. A large proportion of these forests consists of young planted forests (PFs), which have significant potential as carbon sinks. Yet given the declining carbon accumulation rates as forests mature and limited land for further planting, how best to manage these forests to maximize their future carbon uptake remains poorly studied. Here we employed fine-resolution satellite data, forest growth models, and machine learning to identify key drivers of carbon accumulation. Terrain variables were identified as the most important drivers, followed by climate conditions and soil nutrients. We further assessed the carbon sink potential under five forest management scenarios, each involving different harvest and regeneration strategies. Our results indicate that under the optimal scenario with the highest carbon sink potential, harvesting PFs over a 20-year period and progressively replanting each year could yield a potential carbon stock of 0.53 ± 0.01 PgC by 2060, without expanding forest cover. This represents 2.5 times greater than the baseline scenario, where all PFs and are simply preserved. Our findings suggest that a progressive management approach with a well-planned rotation period could significantly enhance carbon sequestration in planted forests.